Isolation and Characterization of Novel Sulfate-Reducing Bacterium Capable of Anaerobic Degradation of p-Xylene - Higashioka, Yuriko (Japanese Society of Microbial Ecology/The Japanese Society of Soil Microbiology, 2012)
A novel strain of p-xylene-degrading sulfate reducer was isolated in pure culture. Strain PP31 was obtained from a p-xylene-degrading enrichment culture established from polluted marine sediment. Analyses of the 16S rRNA gene and two functional genes involved in sulfate respiration and anaerobic degradation of aromatic compounds revealed that the isolate was closely related to members of the genus Desulfosarcina. Strain PP31 was capable of growing on p-xylene under sulfate-reducing conditions, and the ratio of generated sulfide and consumed p-xylene suggested complete oxidation by the novel isolate. The strain could not grow on benzene, toluene, ethylbenzene, m-xylene o-xylene, or n-hexane as an electron donor. Strain PP31 is the first isolated bacterium that degrades p-xylene anaerobically, and will be useful to understanding the mechanism of anaerobic degradation of p-xylene.